2019
DOI: 10.1590/2317-1782/20192018217
|View full text |Cite
|
Sign up to set email alerts
|

Bilinguismo e reconhecimento de fala no silêncio e no ruído em adultos

Abstract: RESUMOObjetivo: Comparar a habilidade de reconhecimento de sentenças no silêncio e no ruído em indivíduos normo-ouvintes monolíngues, falantes do português brasileiro e, bilíngues, falantes do português brasileiro e do alemão, e do português brasileiro e italiano, bem como analisar a influência do período de aquisição da segunda língua no desempenho dos bilíngues. Método Participaram da pesquisa 87 indivíduos entre a faixa etária de 18 e 55 anos de idade, normo-ouvintes, os quais foram distribuídos em: grupo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Finally, there was an effect of multilingualism on speech intelligibility in the noisiest session, and it can be concluded that subjects who speak more than one language decode the speech signals better. This is in accordance with previous literature demonstrating that bilingual individuals have more developed executive functions of inhibitory control, attention, and memory, compared to monolingual individuals (11) . These subjects have greater sensitivity to audiovisual speech stimuli and greater accuracy in phoneme perception, which consequently leads to a greater activation of speech-related neuronal networks (10)(11)(12) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Finally, there was an effect of multilingualism on speech intelligibility in the noisiest session, and it can be concluded that subjects who speak more than one language decode the speech signals better. This is in accordance with previous literature demonstrating that bilingual individuals have more developed executive functions of inhibitory control, attention, and memory, compared to monolingual individuals (11) . These subjects have greater sensitivity to audiovisual speech stimuli and greater accuracy in phoneme perception, which consequently leads to a greater activation of speech-related neuronal networks (10)(11)(12) .…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous literature demonstrating that bilingual individuals have more developed executive functions of inhibitory control, attention, and memory, compared to monolingual individuals (11) . These subjects have greater sensitivity to audiovisual speech stimuli and greater accuracy in phoneme perception, which consequently leads to a greater activation of speech-related neuronal networks (10)(11)(12) . It is therefore hypothesized that the benefit observed here was related to improved executive function in general, and phoneme processing ability in particular, in those who speak more than one language.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation